Genotypic Difference in Growth and Yield Related Traits of Onion (Allium Cepa L.) Varieties at Southern Tigray - Gebremeskel, Haileslassie; Abebe, Haile; Jaleto, Kedir; Biratu, Wakuma (Current Research in Agricultural Sciences, 2016)
Onion (Allium cepa L.) is the most common member of the family Amaryllidaceae (Alliaceae) which grows as a herbaceous biennial vegetable crop with cross pollinated and monocotyledonous behavior having diploid chromosomes number 2n=16. In order to identify Genotypic difference in growth, yield and yield related traits of Onion varieties, the field experiment was carried out at the research station of Mehoni Agricultural Research Center, southern, Ethiopia in the 2013 and 2014 cropping season under irrigation condition. The experiment was consisted of varieties of onion arranged in completely randomized block design with four replications. In 2013 cropping season, days to 50% maturity, bulb diameter and unmarketable were significantly affected by varietal difference. On the other hand, marketable yield, unmarketable yield and total yield were also influenced through varietal effect in 2014. The highest marketable yield (318.52 q ha-1) was obtained from Adama red variety; which, however, it was statistically on par with the marketable yield (289.26 q ha-1) at Nafis variety whereas the lowest marketable yield (222.41 q ha-1) was recorded at Nasik red variety in 2014 cropping season.